2001
DOI: 10.1097/00000542-200106000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction of Opioid-induced Cardioprotection in Ischemia-Reperfusion

Abstract: Stimulation of delta1-opioid receptors generates oxygen radicals via mitochondrial KATP channels. This signaling pathway attenuates oxidant stress and cell death in cardiomyocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 0 publications
1
19
0
2
Order By: Relevance
“…Radicals are released from the mitochondria as a consequence of K ATP channel opening (Duranteau et al, 1998;Kowaltowski et al, 2001;McPherson and Yao, 2001a). Activation of opiate receptors by morphine leads to activation of mitochondrial K ATP channels followed by an increase of intracellular free radical formation (McPherson and Yao, 2001a;2001b). Furthermore, protein kinase C can be activated by free radicals (Gopalakrishna and Anderson, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Radicals are released from the mitochondria as a consequence of K ATP channel opening (Duranteau et al, 1998;Kowaltowski et al, 2001;McPherson and Yao, 2001a). Activation of opiate receptors by morphine leads to activation of mitochondrial K ATP channels followed by an increase of intracellular free radical formation (McPherson and Yao, 2001a;2001b). Furthermore, protein kinase C can be activated by free radicals (Gopalakrishna and Anderson, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of morphine on ionic currents in cardiac myocytes have shown not to depend on opioid receptor 24 or to be mediated via d-and k-receptors 25 . However, its cardioprotective effect is known to be due to the activation of d-receptors 26,27 . Studies have shown that opioids like dextropropoxiphene, pethidine and leucine enkephalin reduce I Ca-L but only the inhibition induced by d-receptor agonist (leucine enkephalin) was blocked by naloxone 28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous administration of 3 mg morphine after the onset of myocardial infarction reduced the serum ICAM-1 level. 90 However it is of note that there have been reports which showed that halogenated anesthetics 43 and opioids 83 were not protective when administered after the onset of ischemia. Overall, it is still controversial whether anesthetics protect the heart when administered after the onset of ischemia.…”
Section: Neutrophil Adhesion and Migrationmentioning
confidence: 98%
“…Conversely protection by morphine and fentanyl is abolished by *-antagonists. 64,67,78,83 The role of 6-receptors remains controversial. 75,86,88,89 Whether µ-receptors contribute to cardioprotection in humans is not known.…”
Section: Preconditioningmentioning
confidence: 99%
See 1 more Smart Citation